Synthesis of nanostructured cupric oxide for visible light assisted degradation of organic wastewater pollutants. Issue 1 (1st January 2021) - Dodoo-Arhin, David; Mbu, Etchu E.; Ntwampe, Seteno K.; Malenga, Edward N.; Fosso-Kankeu, Elvis; Agyei-Tuffour, Benjamin; Nyankson, Emmanuel; Yaya, Abu; Agbe, Henry
Abstract: When organic dye-containing wastewater from textile industries are sometimes released into the environment, the liquids tend to pollute the environment whilst their solid residue accrues on land after the evaporation of the water. Most of these synthetic compounds are known to be poisonous and carcinogenic to living organisms. For this study, a relatively simple, sustainable and cost-effective approach have been utilized to synthesize CuO nanoparticles using copper precursor salts: (CuSO4 .5H2 O) and (Cu(NO3 )2 .3H2 O), as a remedy for dye pollution reduction in water. Due to their simplicity of synthesis, insignificant harmfulness and cost, copper (II) oxide (CuO) nanoparticles were used to breakdown three generally utilized dyes; Rhodamine B (RhB), Methylene Blue (MB)- [Methylthioninium chloride] and Methyl Orange (MeO). The as-prepared nanoparticles were characterized to determine the ordered arrangement of atoms, functional groups, weight loss, thermal properties, microstructure and surface characteristics. Most significantly, the predominant preferential crystal growth was along the {002}/{-111} plane for the sulphate-based precursor whiles for the nitrate based precursor, it was preferentially grown along the {111} direction. The mesoporous nanoparticles had average crystallite sizes of 12 nm and 15 nm; and BET surface areas of 42.9 m 2 /g, and 69.6 m 2 /g respectively. The as-prepared nanoparticles were assessed for their photocatalytic behaviour in response to visible light exposure for 100 minutes at 25-min' intervals. The nitrate precursor-based CuO photocatalysts showed relatively higher photodegradation efficiency (MeO-94.3%; MB- 90.6%; RhB - 99.6%) as compared with the sulphate precursor-based CuO photocatalysts (MeO-85.2 %; MB- 87.9%; RhB- 98.8%).